PEMBAGIAN HARTA WARIS MENURUT HUKUM ADAT DAN HUKUM ISLAM DI KECAMATAN CEMPAKA KABUPATEN OKU TIMUR - Julian Harris Djauhary (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
In terms of kinship, people in Cempaka East OKU District generally base  family lineage from men side (father), or Patrilineal. The main problems in this thesis are: how is the distribution of inheritance under customary law and islamic law in Cempaka Sub-district, East OKU district? Anf how is the application of Islamic Law on the distribution of customary inheritance in  Cempaka Sub-district, East OKU District? This thesis is a sociological /empirical law research. Inthis study  it is examined how the system of the distribution of inheritance is applied or implemented in Cempaka sub-district, East OKU district, and what the role of Islamic Law on the distribution is. The data collection method is through documentation study, direct data collection by giving structured questionnaires and conducting interviews with respondents.Based on data processing, this study can be concluded as follows:1)                  The distribution of inheritance in Cempaka sub-district East OKU district has been done by following procedures of Komering family, which is applicable customary law in Cempaka sub-district, in which successor system is mostly used, where all properties of the parents (heir) will become the inheritance. The inheritance has been forwarded or distributed to the heirâ€™s children. Some other Komering people in Cempaka sub-district divide the inheritance if the owner has already passed away. Customary inheritance law in Cempaka sub-district East OKU district still exists and is still in use even if the procedure is unsure, however it is still in compliance to customs rules although it almost changes. The position of traditional leaders or customary leaders in the distribution of inheritance has almost no function, because people believe that inheritance distribution issue is not their expertise. Most people in Cempaka sub-district East OKU district have already known that inheritance is also a part of religiousissues, namely Islam, so inheritance distribution issue is a religious issue. This means it falls under Islamic Law. Based on that statement, majority of Cempaka sub-district people already implemented the distribution of inheritance based on Islamic Law, though it is not yet entirely according to Al Qurâ€™an and Al Hadits.2)                  The implementation of Islamic Law in the distribution of inheritance according to Islamic Law in Cempaka sub-district has gradually taken place,, and slowly but surely Al Qurâ€™an and Al Hadits guidance in the distribution of inheritance will be done well and will always be a reference.